Moses Mendelssohn's Hebrew writings - Mendelssohn, Moses (Yale Judaica Series, 2018)
Cover -- Half Title -- Title -- Copyright -- CONTENTS -- TRANSLATOR'S ACKNOWLEDGMENTS -- GENERAL NOTES TO THE TRANSLATION -- LIST OF ABBREVIATIONS -- INTRODUCTION: THE MENDELSSOHN MYTH AND THE ASYMMETRICAL RECEPTION OF THE HEBREW WRITINGS -- I. QOHELET MUSAR / PREACHER OF MORALS -- EDITORS' INTRODUCTION -- SELECTIONS -- II. BE'UR MILLOT HA-HIGGAYON / COMMENTARY ON THE TREATISE ON LOGICAL TERMS -- EDITORS' INTRODUCTION -- SELECTIONS -- III. MEGILLAT QOHELET / COMMENTARY ON ECCLESIASTES -- EDITORS' INTRODUCTION -- SELECTIONS -- IV. SEFER NETIVOT HA-SHALOM / THE PATHS OF PEACE -- EDITORS' INTRODUCTION -- OR LI-NETIVAH / A LIGHT FOR THE PATH: A GENERAL INTRODUCTION TO ALL FIVE BOOKS [OF THE PENTATEUCH] -- SELECTIONS FROM GENESIS -- SELECTIONS FROM EXODUS -- SELECTIONS FROM LEVITICUS, NUMBERS, AND DEUTERONOMY -- ADDITIONAL BIBLIOGRAPHY -- GLOSSARY -- A -- B -- C -- E -- G -- H -- I -- J -- K -- L -- M -- N -- O -- R -- S -- T -- W -- Y -- Z -- GENERAL INDEX -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z -- INDEX OF SOURCES